The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22020613
|View full text |Cite
|
Sign up to set email alerts
|

2-(2-Methyl-2-nitrovinyl)furan but Not Furvina Interfere with Staphylococcus aureus Agr Quorum-Sensing System and Potentiate the Action of Fusidic Acid against Biofilms

Abstract: Quorum sensing (QS) plays an essential role in the production of virulence factors, in biofilm formation and antimicrobial resistance. Consequently, inhibiting QS is being considered a promising target for antipathogenic/anti-virulence therapies. This study aims to screen 2-nitrovinylfuran derivatives structurally related to Furvina (a broad-spectrum antibiotic already used for therapeutic purposes) for their effects on QS and in biofilm prevention/control. Furvina and four 2-nitrovinylfuran derivatives (compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…A careful literature overview highlighted some research studies based on the LytTR domain of the apo AgrA structure from S. aureus (PDB code 4G4K) performed by Leonard and co-workers [74], and a previous study (PDB code: 3BS1) [97], which reported the crystal structure of the DNA-binding domain of S. aureus AgrA complexed with a DNA pentadecamer duplex. On these bases we evaluated all the PDB structures in the PDB selecting 4G4K [74,76,[98][99][100]. Our approach was to evaluate the best resolution of this structure (1.52 Å) among the others, and the different conformations that the protein can assume depending to the presence or the absence of bound DNA.…”
Section: Discussionmentioning
confidence: 99%
“…A careful literature overview highlighted some research studies based on the LytTR domain of the apo AgrA structure from S. aureus (PDB code 4G4K) performed by Leonard and co-workers [74], and a previous study (PDB code: 3BS1) [97], which reported the crystal structure of the DNA-binding domain of S. aureus AgrA complexed with a DNA pentadecamer duplex. On these bases we evaluated all the PDB structures in the PDB selecting 4G4K [74,76,[98][99][100]. Our approach was to evaluate the best resolution of this structure (1.52 Å) among the others, and the different conformations that the protein can assume depending to the presence or the absence of bound DNA.…”
Section: Discussionmentioning
confidence: 99%
“…It involves multiple signal transduction pathways that regulate biofilm formation, virulence, motility, and sporulation [ 48 ]. In S. aureus , the research on QS system mainly focused on the accessory regulatory factor (Agr) system and LuxS/autoinducer-2 (AI-2) system [ [71] , [72] , [73] ].…”
Section: Promising Targets In the Regulation Of S Aureus ...mentioning
confidence: 99%
“…Unlike the mainstream antibiotics described above, relatively few studies have been conducted on the combination of fusidic acid (FA) or clindamycin (CD) with QSIs. However, this drug combination provides a new direction for the fight against S. aureus or its resistant strains [72][73][74].…”
Section: Combination Of Other Antibiotics and Qsismentioning
confidence: 99%
“…In addition, for strains and different concentrations of 63 and 62, most bacteria maintain membrane integrity (more than 70%), which is essential for the effective treatment of bacterial infections. Nevertheless, the synergistic mechanism between FA and 62 or 63 remains to be understood [72].…”
Section: Combination Of Other Antibiotics and Qsismentioning
confidence: 99%